1999
DOI: 10.1038/sj.bjc.6690680
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-induced changes in energy metabolism and viability of melanoma cells

Abstract: Summary Cancer cells are characterized by a high rate of glycolysis, which is their primary energy source. We show here that a rise in intracellular-free calcium ion (Ca 2+ ), induced by Ca 2+ -ionophore A23187, exerted a deleterious effect on glycolysis and viability of B16 melanoma cells. Ca 2+ -ionophore caused a dose-dependent detachment of phosphofructokinase (EC 2.7.1.11), one of the key enzymes of glycolysis, from cytoskeleton. It also induced a decrease in the levels of glucose 1,6-bisphosphate and fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…The present study elucidates one of the molecular mechanisms for H 2 S-induced preservation of mitochondrial function. A previous study found that A23187 stimulates mitochondrial ATP production via increased activity of mitochondria-bound hexokinase (37). As shown here, A23187 also stimulates ATP production in part through mitochondrial translocation of CSE in vascular SMCs.…”
Section: Discussionsupporting
confidence: 48%
“…The present study elucidates one of the molecular mechanisms for H 2 S-induced preservation of mitochondrial function. A previous study found that A23187 stimulates mitochondrial ATP production via increased activity of mitochondria-bound hexokinase (37). As shown here, A23187 also stimulates ATP production in part through mitochondrial translocation of CSE in vascular SMCs.…”
Section: Discussionsupporting
confidence: 48%
“…An up‐regulation of L‐type channel Ca v 1.2 mRNA has been reported in colorectal cancer (Wang et al., 2000), whereas the enhanced expression of Ca v 3.1 and/or Ca v 3.2 T‐type channels are common findings in a variety of tumour cells (see Taylor et al., 2008a for review). In melanoma cells, the expression of VGCCs has not been investigated thoroughly, even when available evidence indicates that Ca 2+ signalling plays an important role in their viability and motility (Cox et al., 2002; Deli et al., 2007; Glass‐Marmor et al., 1992). In the present study we examined whether VGCCs are functionally expressed in melanoma and play a critical role in the homeostasis of these cells.…”
Section: Introductionmentioning
confidence: 99%
“…16 On the other hand, intracellular Ca 21 oscillations are critical for the survival and migration of melanoma cells. 17,18 The melanocytic linage is characterized by a special resistance to apoptosis, which might be even attenuated during malignant transformation. It is now well established that apoptosis regulatory proteins B-cell lymphoma/leukemia-2 gene/Bax are regulators of the endoplasmic reticulum (ER) Ca 21 stores, and Ca 21 is a key mediator of apoptosis.…”
mentioning
confidence: 99%